An evaluation of a sustained senior mentor program for medical students. Issue 3 (3rd July 2022) - Ratner, Edward R.; Kilaberia, Tina R.; Englund, June; Fink, Howard A.
ABSTRACT: Background/Objective Medical student geriatrics education using community-based volunteer older persons, known as a Senior Mentor Program (SMP), began decades ago. Though these programs have been described and evaluated against curriculum objectives, the full breadth of students' learning from SMPs has not been reported. Methods We conducted a qualitative study using content analysis of reflections of Year 2 medical students submitted during a single visit home-based SMP. Written reflections of 102 randomly selected students from 2016–2018 were inductively coded and grouped into themes. Older persons from the SMP site assisted in coding and quotation selection. Results We discerned six themes from the evaluation of student reflections: student insight, interview and exam, social community, challenges with aging, strengths (responses to challenges), and physical infrastructure. Conclusion A single home visit with older adults enables pre-clinical medical students to learn about multiple positive aspects of aging.